Venous Thromboembolism in Foot and Ankle Surgery: How Common is It?. Issue 4 (November 2022) - Martinazzi, Brandon J.; Nam, Hannah; Mansfield, Kirsten N.; Dopke, Kelly; Ptasinski, Anna; Kirchner, Gregory; Manto, Kristen; Aynardi, Michael C.
Category: Other; Ankle; Ankle Arthritis; Bunion; Sports Introduction/Purpose: Venous thromboembolism (VTE) is a feared complication following orthopaedic surgery. The limited research exploring the rate of VTE following different types of foot and ankle surgery makes it difficult to establish clear guidelines for prescribing VTE prophylaxis. Therefore, the purpose of this study was to determine the rate of VTE in patients undergoing various types of foot and ankle procedures. Methods: A large online retrospective database that utilizes ICD and CTP codes was queried to determine the rate of VTE that occurred within 1-month of surgery in common foot and ankle procedures. Surgeries investigated included: Arthrodesis, Total Ankle Arthroplasty, Bunionectomy, Hammer Toe Correction, Watson-Jones, and Achilles repair. Only patients that did not receive postoperative anticoagulation or antiplatelet agents were included in the analysis. Demographic data was also collected. Results: From 2011 to 2022, 27, 872 patients underwent Arthrodesis, 1, 513 had a Total Ankle Arthroplasty, 31, 808 had a Bunionectomy, 26, 828 had Hammer Toe correction, 7, 545 had a Watson-Jones procedure, and 8, 770 had an Achilles repair. Of these procedures, Achilles repair had the highest rate of postoperative VTE (1.32%), followed by Watson-Jones (1.21%), Arthrodesis (0.89%), Ankle Arthroplasty (0.86%), Hammer Toe (0.76%) and Bunionectomy (0.65%). The overall rate of VTE in all procedures was found to be 0.84% (880/104, 336). Conclusion: Venous thromboembolism is a serious complication following foot and ankle surgery. The unknown incidence of VTE in common foot and ankle surgeries may contribute to the lack of clear guidelines for prescribing VTE prophylaxis. This study helps to define rates of VTE in patients not receiving prophylaxis that underwent Arthrodesis, Ankle Arthroplasty, Bunionectomy, Hammer Toe, Watson-Jones, and Achilles repair. More studies are needed to help establish clear guidelines for foot and ankle surgeons to follow.